Eating Behaviors and Physical Activity in Children Aged 7-10 Years - Żyłka, K.; Owczarek, T.; Platta, A.; Kozirok, W. (Scientific Journal of Gdynia Maritime University, 2017)
The aim of the present study was to assess eating behaviors and leisure time physical activity in children aged 7–10 years.The survey was conducted in a group of 107 parents of children attending grades 1–3 of primary school. A self-designed questionnaire was used as a research tool. Statistical analyses were carried out with the use of Spearman’s correlation test and Mann-Whitney U-test, with adopting α = 0,05 as showing significance. The study showed that 65% of children ate breakfast on a daily basis. The majority of pupils ate 4 meals a day. Current recommendations regarding vegetables consumption were followed by 25% of children, regarding fruits – by 32% and regarding fish – only by 10% of children. Over a half of pupils ate sweets at least once a day. Participation in leisure time physical activity on a daily basis was recorded only in 16% of children, whilst 48% of children were engaged in physical activity 2–3 times a week. As the results of the study indicated, children’s eating behaviors were mostly improper. Participation in leisure time physical activity was found to be low. These factors could adversely affect children’s development.